(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
This article analyzes the cultural-dialectical characteristics of students in the process of interaction between Internet culture and national identity. The study reveals how the worldview, values, and social behavior of young people are formed in the process of using the Internet, as well as the harmony and contradictions between global information flows and national culture. The article also highlights the importance of students’ cultural identity, information selection skills, and critical thinking levels in the context of globalization. The results of the study will serve to develop scientific and practical recommendations for raising the younger generation in the spirit of spiritual maturity in the Internet space.